The truncated TNL receptor TN2‐mediated immune responses require ADR1 function. (28th August 2021) - Wang, Wei; Liu, Na; Gao, Chenyang; Rui, Lu; Jiang, Qiaochu; Chen, Shuling; Zhang, Qin; Zhong, Guitao; Tang, Dingzhong
SUMMARY: The loss of function of exocyst subunit EXO70B1 leads to autoimmunity, which is dependent on TIR‐NBS2 (TN2), a truncated intracellular nucleotide‐binding and leucine‐rich repeat receptor (NLR). However, how TN2 triggers plant immunity and whether typical NLRs are required in TN2‐activated resistance remain unclear. Through the CRISPR/Cas9 gene editing system and knockout analysis, we found that the spontaneous cell death and enhanced resistance in exo70B1‐3 were independent of the full‐length NLR SOC3 and its closest homolog SOC3‐LIKE 1 (SOC3‐L1). Additionally, knocking out SOC3‐L1 or TN2 did not suppress the chilling sensitivity conferred by chilling sensitive 1‐2 ( chs1‐2 ). The ACTIVATED DISEASE RESISTANCE 1 (ADR1) family and the N REQUIREMENT GENE 1 (NRG1) family have evolved as helper NLRs for many typical NLRs. Through CRISPR/Cas9 gene editing methods, we discovered that the autoimmunity of exo70B1‐3 fully relied on ADR1s, but not NRG1s, and ADR1s contributed to the upregulation of TN2 transcript levels in exo70B1‐3 . Furthermore, overexpression of TN2 also led to ADR1‐dependent autoimmune responses. Taken together, our genetic analysis highlights that the truncated TNL protein TN2‐triggered immune responses require ADR1s as helper NLRs to activate downstream signaling, revealing the importance and complexity of ADR1s in plant immunity regulation. Significance Statement: In this study, we found that the truncated NLR protein TN2‐activated immune responses in exo70B1‐3 required helper RNL proteins ADR1s, but not NRG1s. The expression of TN2 in exo70B1‐3 was regulated by ADR1s in a positive feedback loop. Overexpression of TN2 also led to ADR1‐dependent autoimmunity in Arabidopsis. These data uncovered that the resistance mediated by the TN‐type protein TN2 requires ADR1s as helper NLRs, revealing the importance and complexity of ADR1s in plant immunity regulation.